ANALISIS IMPLEMENTASI GAYA KEPEMIMPINAN TRANSFORMASIONAL UNTUK PENINGKATAN KUALITAS PELAYANAN FARMASI : KAJIAN LITERATUR - Astuti, Rina; Faeni, Dewi Puspaningtyas (SINERGI : Jurnal Riset Ilmiah, 2025)
This study aims to analyze the role of transformational leadership in improving the quality of pharmacy services in hospitals through a comprehensive literature review. Modern pharmaceutical services have evolved into patient-oriented services, making patient satisfaction and service quality key indicators of success. Leadership style, particularly transformational leadership, is considered crucial in shaping work culture and motivating staff to achieve organizational goals. The method used was a qualitative literature study, analyzing relevant scientific articles from 2019-2024 found in the Google Scholar database. Of the 80 articles found, 9 were reviewed in-depth. The literature synthesis results indicate that transformational leadership, through its four main dimensions (idealized influence, inspirational motivation, intellectual stimulation,individual consideration), has a significant impact on improving the quality of pharmacy services.  The implementation of this leadership style has been shown to increase the motivation, commitment, and professionalism of pharmacists. This has a direct impact on improving technical quality (prescription accuracy), interpersonal quality (patient communication), and service efficiency. Although challenges such as resistance to change exist, supporting factors such as an open organizational culture and ongoing leadership training can facilitate successful implementation. In conclusion, developing transformational leadership competencies for pharmacy managers is a strategic step to achieve excellent pharmaceutical service.